Inflammatory Reactions to Red Tattoo Inks: Three cases highlighting an emerging problem - Ruiz-Villaverde, Ricardo (Sultan Qaboos Univ Med J, 2018)
In recent years, tattoos have become more commonplace. However, this can result in various inflammatory processes, the management of which can be challenging in daily clinical practice. Tattoo-related inflammatory reactions can comprise different patterns, including acute and immediate reactions, foreign body granulomas, sarcoid granulomas, isomorphic lesions, allergic contact dermatitis and photosensitivity. We report three cases who were referred to the Dermatology Outpatient Clinic of the Hospital Universitario San Cecilio, Granada, Spain, in 2017 with various skin reactions in the red-ink areas of their tattoos. Screening was performed for infectious diseases like atypical mycobacterial infections and systemic processes such as sarcoidosis. A good therapeutic response was achieved in all cases. An adequate differential diagnosis is essential for the therapeutic management of this emerging health problem.